Efficient Strategy for Detecting Gene × Gene Joint Action and Its Application in Schizophrenia. Issue 1 (23rd November 2013) - Won, Sungho; Kwon, Min‐Seok; Mattheisen, Manuel; Park, Suyeon; Park, Changsoon; Kihara, Daisuke; Cichon, Sven; Ophoff, Roel; Nöthen, Markus M.; Rietschel, Marcella; Baur, Max; Uitterlinden, Andre G.; et al.
ABSTRACT We propose a new approach to detect gene × gene joint action in genome‐wide association studies (GWASs) for case‐control designs. This approach offers an exhaustive search for all two‐way joint action (including, as a special case, single gene action) that is computationally feasible at the genome‐wide level and has reasonable statistical power under most genetic models. We found that the presence of any gene × gene joint action may imply differences in three types of genetic components: the minor allele frequencies and the amounts of Hardy‐Weinberg disequilibrium may differ between cases and controls, and between the two genetic loci the degree of linkage disequilibrium may differ between cases and controls. Using Fisher's method, it is possible to combine the different sources of genetic information in an overall test for detecting gene × gene joint action. The proposed statistical analysis is efficient and its simplicity makes it applicable to GWASs. In the current study, we applied the proposed approach to a GWAS on schizophrenia and found several potential gene × gene interactions. Our application illustrates the practical advantage of the proposed method.